Learning During The Covid-19 Pandemic: Proceeding Student Learning Interests And The Continuity Of Face-To-Face Learning - Aulia Nurisfah; Imam Tabroni; Faithful Hermin Rini; Nida Hoerunisa (IHSA Institute, 2022)
Study this aim for analyze interest study student on period pandemic to continuity study stare advance in MI Khairunnas. Study this use method study qualitative with subject study that is student on class 3. Technique collection data with use interview and observation. Technique interview that is with give live question to student. Technique analysis data with use observation on Pandemic covid-19 in Indonesia which bring impact or nope to interest study student. When process learning switch with learning online many student which no like again study in school, no a little also which sigh feel more interest study in house. Learning distance far even resulted interest study student Becomes decrease be marked with lack of participation active student when follow process learning in class. After learning online implemented not enough more During 2 year, pandemic covid 19 even already start disappear and activity study teach even already start held with stare advance return, will but when process learning held with stare advance student no live can study as normal his when learning stare advance before pandemic covid-19, they must adapt return because possible already used to with study online. Students are still used to the atmosphere when online, so during the learning process going on interest haven't learned yet fully prepared. By because of that, very teacher role in implementation process learning in a manner face to face again, teacher role in guide students for return spirit, motivation and interest study his, give facilities in the form of always providing motivation and enthusiasm before learning in start every day, motivating student so that spirit study return, help sert supervise student when carry out process learning so that student follow process learning with good and correct, so that could obtain results learning which optimal.